2018
DOI: 10.3390/ma11091680
|View full text |Cite
|
Sign up to set email alerts
|

Novel Porous Phosphorus–Calcium–Magnesium Coatings on Titanium with Copper or Zinc Obtained by DC Plasma Electrolytic Oxidation: Fabrication and Characterization

Abstract: In this paper, the characteristics of new porous coatings fabricated at three voltages in electrolytes based on H3PO4 with calcium nitrate tetrahydrate, magnesium nitrate hexahydrate, and copper(II) nitrate trihydrate are presented. The SEM, energy dispersive spectroscopy (EDS), glow discharge optical emission spectroscopy (GDOES), X-ray photoelectron spectroscopy (XPS), and XRD techniques for coating identification were used. It was found that the higher the plasma electrolytic oxidation (PEO) (micro arc oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 133 publications
0
12
0
Order By: Relevance
“…In this study, the EDS scan found that the proportion of magnesium on titanium sheets increased with increasing magnesium concentration in the electrolyte, and the ion distribution on the surface of the material could be adjusted by adjusting the ion concentration in the electrolyte. 25 The SEM images revealed that the addition of Mg 2+ ions did not destroy the microporous morphology formed by MAO. The roughness and contact angle of the material do not change with the increasing of magnesium.…”
Section: Discussionmentioning
confidence: 92%
“…In this study, the EDS scan found that the proportion of magnesium on titanium sheets increased with increasing magnesium concentration in the electrolyte, and the ion distribution on the surface of the material could be adjusted by adjusting the ion concentration in the electrolyte. 25 The SEM images revealed that the addition of Mg 2+ ions did not destroy the microporous morphology formed by MAO. The roughness and contact angle of the material do not change with the increasing of magnesium.…”
Section: Discussionmentioning
confidence: 92%
“…It should be pointed out that authors have contribution in development of PEO processes with usage of concentrated (85%) orthophosphoric acid instead of water as an electrolyte with additives such as Ca(NO 3 ) 2 , Mg(NO 3 ) 2 , Zn(NO 3 ) 2 and Cu(NO 3 ) 2 under both DC [158,159] and AC [160] conditions. In case of use of electrolyte that contains all four nitrates under DC conditions, it was found out that additional metal ions from electrolyte occurs in obtained porous surfaces amorphic phase while Ti 2 P 2 O 7 occurs in crystalline phase.…”
Section: Peo Coatings Enriched With Phosphorus Calcium and Magnesiummentioning
confidence: 99%
“…The use of Cu(NO 3 ) 2 •3H 2 O salt with concentrated H 3 PO 4 (85 wt%) as the electrolyte in the PEO process allowed us to obtain the extended surface structures of the porous characteristics containing compounds of copper and phosphorus on the Ti6Al4V alloy surface. The researchers indicated that the content of copper(II) nitrate(V) trihydrate essentially affected both the surface geometry and the composition of the obtained coatings [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%